Lipid droplet accumulation in β cells in patients with type 2 diabetes is associated with insulin resistance, hyperglycemia and β cell dysfunction involving decreased insulin granules - Horii, Tomomi; Kozawa, Junji; Fujita, Yukari; Kawata, Satoshi; Ozawa, Harutoshi; Ishibashi, Chisaki; Yoneda, Sho; Nammo, Takao; Miyagawa, Jun-ichiro; Eguchi, Hidetoshi; Shimomura, Iichiro (Frontiers in Endocrinology, 2022)
Background and objective: Pancreatic fat is a form of ectopic fat. Lipid droplets (LDs) are also observed in β cells; however, the pathophysiological significance, especially for β cell function, has not been elucidated. Our aim was to assess LD accumulation in β cells in various stages of glucose intolerance and to clarify its relationship with clinical and histological parameters. Background and objective: Pancreatic fat is a form of ectopic fat. Lipid droplets (LDs) are also observed in β cells; however, the pathophysiological significance, especially for β cell function, has not been elucidated. Our aim was to assess LD accumulation in β cells in various stages of glucose intolerance and to clarify its relationship with clinical and histological parameters. Methods: We examined 42 Japanese patients who underwent pancreatectomy. The BODIPY493/503-positive (BODIPY-positive) area in β cells was measured in pancreatic sections from 32 patients. The insulin granule numbers were counted in an additional 10 patients using electron microscopy. Results: The BODIPY-positive area in β cells in preexisting type 2 diabetes patients was higher than that in normal glucose tolerance patients (p = 0.031). The BODIPY-positive area in β cells was positively correlated with age (r = 0.45, p = 0.0097), HbA1c (r = 0.38, p = 0.0302), fasting plasma glucose (r = 0.37, p = 0.045), and homeostasis model assessment insulin resistance (r = 0.41, p = 0.049) and negatively correlated with an increase in the C-peptide immunoreactivity level by the glucagon test (r = -0.59, p = 0.018). The ratio of mature insulin granule number to total insulin granule number was reduced in the patients with rich LD accumulation in β cells (p = 0.039). Conclusions: Type 2 diabetes patients had high LD accumulation in β cells, which was associated with insulin resistance, hyperglycemia, aging and β cell dysfunction involving decreased mature insulin granules.